Crafting Solidarities, Crafting a Zine: Methods for Resistance and Recovery in Higher Education amongst Doctoral Researchers of Colour - Ghaffar, Farhana; Kamtam, Madhuri; Mir, Touseef; Nakibuuka, Linda-Marie; Priyadharshini, Esther; Ramakrishnan, Kavita; Martinez Renteria, Abigail; Thomas, Teemol; Wang, Qingru (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
How does the process of producing a zine contribute to resistance and action to create new spaces of solidarity? This article reflects on such a process to account for the experiences of the ‘Concrete Collective,’ a research collective of staff and doctoral researchers of colour. The project was initiated to understand what 'belonging' can mean, or fail to mean, when inhabiting the spaces of UK Higher Education (HE). A key output of this project was our co-produced zine, which became a means to express the collective’s distinctive journeys through HE and experiences of (un)belonging within and beyond the university. In this article, we reflect on how we worked to create a safe space within the institution and how arts-based making practices were central to expressing experiences not easily communicated through more traditional methods; using these collaborative and creative methods generated learning encounters, producing not only material for the zine but a new sense of community beyond the institutionalized spaces available within a university. The act of crafting the zine went together with learning to imagine, understand, think, and feel as a collective. We explore how the physical and political act of zine-ing provided a space to collectively critique and resist isolationist tendencies that create a sense of unbelonging amongst historically under-represented groups within HE. This act of creation allowed us to critically reflect on the dynamics of how solidarities may be produced. Finally, we reflect on the possibilities of nurturing and sustaining solidarities and collective spaces while carefully attending to hierarchical relationships present within the university.